KINETIC STUDY OF BIOSORPTION OF ARSENIC FROM SOIL USING MICROORGANISMS - E. Atikpo; J. E. Agori; M. T. Peretomode; A. Micheal; E. C. Ofonedu (NIJOTECH, 2019)
This work studied the kinetics of biosorption of arsenic (As) from polluted soils using two bacteria [Proteus mirabilis (P. mirabilis) and Bacillus subtilis (B. subtilis)]. The bacteria obtained from the soils were cultured and utilized to treat the arsenic polluted soils through the process of batch biosorption experiment. The experimental data were fitted with four kinetic models (Pseudo-first order, pseuodo-second order, Elovich and the intra-particle diffusion); and judgement on models performance was made using the values of the models’ coefficient of determination (R2).The four models tested were adequate for describing the biosorption kinetics but the leading performance of the intraparticle diffusion model with R2 of 0.991 for sorption by P. mirabilis and 0.972 for sorption by B. subtilis proved the diffusion process to be the rate-limiting step. This indicated that the systems were transport controlled.
Keywords: Arsenic; contaminated soils; biosorption; sorption kinetics; microorganisms.